2020
DOI: 10.1097/tld.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Class Literacy Instruction for Children With Speech and Language Difficulties

Abstract: This study investigated the response to class-wide phonological awareness and oral language teaching for 40 children who entered school with speech and language difficulties. A stepped wedge research design was adopted to compare the immediate impact of the 10-week teacher-led instruction. The progress of the children with speech and language difficulties was monitored over the first school year and compared with 110 children with language difficulties alone and 95 children with typical development. Children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Accelerated growth for children in Tier 2 towards the levels of their peers was clearly evident. This finding is consistent with previous findings (e.g., Carson et al, 2013;Gillon et al, 2020) that some children require greater support to integrate knowledge about a word's sound structure into their reading and spelling attempts. However, as children were not randomly assigned to Tier 2 vs. control groups in this study, no conclusions around causal relationships can be drawn.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Accelerated growth for children in Tier 2 towards the levels of their peers was clearly evident. This finding is consistent with previous findings (e.g., Carson et al, 2013;Gillon et al, 2020) that some children require greater support to integrate knowledge about a word's sound structure into their reading and spelling attempts. However, as children were not randomly assigned to Tier 2 vs. control groups in this study, no conclusions around causal relationships can be drawn.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence for the BSLA Gillon et al (2019) found that the BSLA significantly accelerated the early literacy achievement of 143 children across seven classrooms with lower levels of oral language when compared to the usual literacy curriculum (where the usual literacy curriculum did include other types of structured phonic and phonological awareness programmes). Further analysis of the performance of all children (i.e., children with typical and lower levels of oral language) showed that children who had received the BSLA earlier in the school year had stronger reading and spelling than children who started the approach 10 weeks later (Gillon et al, 2020). The study reported here replicates and extends these studies with a new cohort of children, teachers, and families.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Engel de Abreu et al emphasized the greater learning difficulties of bilingual students than monolingual students and showed that if cognitive development and cognitive control in the group of bilingual students improves, it will improve their academic performance ( Engel de Abreu et al, 2012 ). Thus, language is one of the most important elements of developmental learning that should develop in a child before primary school and is the basis for his social, economic, and educational life, and language disorders are one of the most controversial groups in the diagnostic category of communication disorders ( Gillon et al, 2020 ). The main diagnostic characteristics of these disorders include language acquisition and use difficulties due to reduced vocabulary, limited sentence structure, and impairment in discourse.…”
Section: Introductionmentioning
confidence: 99%